2021
DOI: 10.2174/1573405616666201223150004
|View full text |Cite
|
Sign up to set email alerts
|

The Differential Diagnostic Value of the Callosal Angle and Evans Index in Mild Cognitive Impairment and Alzheimer's Disease

Abstract: Background: Callosal angle (CA) and Evans index (EI) had been considered as imaging biomarkers to diagnosis normal-pressure hydrocephalus as traditional MR measurement methods. Objective: The current study was aimed to evaluate the differential diagnostic value of CA and EI in the mild cognitive impairment (MCI) and Alzheimer’s disease (AD). Methods: Five-hundred and two subjects were selected from the Alzheimer's Disease Neuroimaging Initiative (ADNI) database, which included 168 normal controls (NC), 23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
(50 reference statements)
0
2
0
Order By: Relevance
“…On the other hand, for NPH patients, EI measurement is a fast and highly reproducible indirect method for assessing VV (Bao et al, 2016 ; Liu et al, 2020 ). VV measurement methods can be direct and indirect (Ambarki et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, for NPH patients, EI measurement is a fast and highly reproducible indirect method for assessing VV (Bao et al, 2016 ; Liu et al, 2020 ). VV measurement methods can be direct and indirect (Ambarki et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…The EI is used as an imaging biomarker of NPH to indirectly assess the VV (Liu et al, 2020 ). A study including 23 definite iNPH patients and 62 healthy elderly volunteers, showed that the correlation between EI and VV and relative VV (RVV) was 0.843 and 0.840, respectively.…”
Section: Discussionmentioning
confidence: 99%